Incorporation of multiple vertical legs in stirrups for shear resistance in wide beams - Murty, D. S. R.; Rao, G. Papa (Journal of Structural Engineering, 2025)
This paper addresses the performance of different stirrup detailings width wise under high shear stresses in wide beams. The occurrence of wide beams is very common. Many structural framing schemes include wide beams. A system of wide beams may provide a simple and economical system to transfer column loads from the tower portion, over required column-free spaces in the podium. In other design situations, architectural limitations may require shallower structural depths, necessitating requirement of more width in beams. Beam shaped pile caps under bridge piers and abutments, and raft beams in shallow foundations need wide beams. In reinforced concrete beams, to resist shear force, efficient spacing limits of stirrup legs along the span and across web are not given, despite the availability of shear specifications in the design codes world over; only a limited number of research studies appear in the literature. In wide beams, shear reinforcement is distributed in more number of vertical legs, instead of two vertical legs as in normal and smaller width beams. The specifications of stirrup leg spacing span wise, provided in IS: 456-20007 relates to only maximum limit. A small number of studies only have directly examined the influence of stirrup spacing across beam width. The results of an experimental programme are presented here, evaluating stirrup vertical leg spacing details used in current practice. Based on the experimental programme, recommendations for detailing of stirrups, width wise in wide beam members are given.